Biogas production with the use of animal manure: a practice for obtaining socioeconomic and environmental benefits - Silva, José Adailton Lima; Pereira, Thaís Mara Souza; Azevedo, Pedro Vieira (Boletim de Geografia, 2021)
Currently, there is a large production of animal waste / manure that is erroneously discarded and often promotes environmental impacts such as pollution of watercourses, which has contributed to the promotion of waterborne diseases. Thus, it has been objectified to use animal manures in an efficient way in the promotion of biogas, which has contributed to provide socio-environmental improvements. Therefore, the present study aimed to analyze the social, economic and environmental benefits of biogas production through the use of biodigesters and how this technology can contribute to the improvement of the lives of rural low-income families. For this, a qualitative research was carried out where, through theoretical and methodological foundations, exploratory and participatory studies were carried out with the rural families in the municipality of Pedra Lavrada-PB, in the semi-arid region of Paraíba. With the studies, it was possible to conclude that the biodigestors: 1) they assemble simple techniques and of easy construction; 2) are low-cost implementation/construction technologies; 3) produces biogas for food cooking, which inhibits costs with the purchase of cooking gas; 4) enables environmental benefits with the use of animal manure - which is renewable - for heat generation, in addition to the use of digestate for soil fertilization; and 5) that biodigestors are a socially disseminable, economically viable, and environmentally sound technology.